Three new species of tribe Odynerini (Hymenoptera, Vespidae, Eumeninae) from the Neotropical Region - Grandinete, Yuri Campanholo; Noll, Fernando Barbosa; Carpenter, James (Zootaxa, 2016)
Three new species from the Neotropical region are described: Ancistroceroides soikai Grandinete & Carpenter, sp. nov. (Costa Rica, Paraguay); Cephalastor huautla Grandinete & Carpenter, sp. nov. (Mexico), and Symmorphus centralis Carpenter & Grandinete, sp. nov. (Costa Rica).